2018
DOI: 10.1007/s00395-018-0684-z
|View full text |Cite
|
Sign up to set email alerts
|

Neural mechanisms in remote ischaemic conditioning in the heart and brain: mechanistic and translational aspects

Abstract: Remote ischaemic conditioning (RIC) is a promising method of cardioprotection, with numerous clinical studies having demonstrated its ability to reduce myocardial infarct size and improve prognosis. On the other hand, there are several clinical trials, in particular those conducted in the setting of elective cardiac surgery, that have failed to show any benefit of RIC. These contradictory data indicate that there is insufficient understanding of the mechanisms underlying RIC. RIC is now known to signal indiscr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(57 citation statements)
references
References 153 publications
(229 reference statements)
0
56
0
1
Order By: Relevance
“…The mechanisms involved in this protective phenomenon might include multiple effectors, such as sympathetic/parasympathetic mechanisms, as bilateral vagotomy was previously shown to abolish cardioprotection induced by RIPC (Basalay et al. ). In addition, increased AKT activity stimulates Kv1.5 potassium channel protein expression at the cell surface (Warsi et al.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanisms involved in this protective phenomenon might include multiple effectors, such as sympathetic/parasympathetic mechanisms, as bilateral vagotomy was previously shown to abolish cardioprotection induced by RIPC (Basalay et al. ). In addition, increased AKT activity stimulates Kv1.5 potassium channel protein expression at the cell surface (Warsi et al.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, this effect was not due to altered blood flow into the ischaemic region [3,71]. The mechanism for this is not known but could potentially involve the parasympathetic nervous system, which is required to convey the signal of remote IPC, and is known to innervate the heart [6]. The shortcomings of ECG are that it does not allow accurate measurement of IS, especially in small animal species, and it probably reflects a combination of both the ischaemic AAR and IS.…”
Section: Measuring Infarct Size In Ischaemic Modelsmentioning
confidence: 99%
“…However, the recent CONDI-2/ERIC-PPCI multicentre trial of RIPC on IS in STEMI patients undergoing primary PCI showed no benefit [46]. Importantly, part of the "remote preconditioning reflex" of RIPC involves activation of the vagal nerve [6,78]. Consequently, vagal nerve stimulation (VNS) should be able to mimic the effects of RIPC.…”
Section: Fig 4 Redistribution Of Coronary Blood Flow Between Ischaemmentioning
confidence: 99%
See 1 more Smart Citation
“…Whether such spatial differences in the magnitude of cardioprotection also exist for more clinically relevant ischemic conditioning maneuvers such as ischemic postconditioning (Zhao et al ), or remote ischemic conditioning prior to (Heusch et al ) or during ischemia (Schmidt et al ) is currently not known. Cardioprotection by remote ischemic conditioning involves vagal nerves (Lieder et al ; Basalay et al ). Therefore, regional differences in cardiac innervation might impact on the magnitude of cardioprotection in septal and anterior free wall compartments.…”
Section: Introductionmentioning
confidence: 99%